Hepatitis C virus and alcohol: Same mitotic targets but different signaling pathways - Alisi, Anna; Ghidinelli, Monica; Zerbini, Alessandro; Missale, Gabriele; Balsano, Clara (Journal of hepatology, 2011)
Chromosomal aberrations are frequently observed in hepatitis C virus (HCV)- and alcohol-related hepatocellular carcinomas (HCCs). The mechanisms by which chromosomal aberrations occur during hepatocarcinogenesis are still unknown. However, these aberrations are considered to be the result of deregulation of some mitotic proteins, including the alteration of Cyclin B1 and Aurora kinase A expression, and the phosphorylation of gamma-tubulin. Our study aims at investigating changes in expression of the above mentioned proteins and related intracellular pathways, in in vitro and in vivo models of both HCV- and alcohol- dependent HCCs. In this study, the molecular defects and the mechanisms involved in deregulation of the mitotic machinery were analyzed in human hepatoma cells, expressing HCV proteins treated or not with ethanol, and in liver tissues from control subjects (n=10) and patients with HCV- (n=10) or alcohol-related (n=10) HCCs. Expression of Cyclin B1, Aurora kinase A, and tyrosine-phosphorylated gamma-tubulin was analyzed in models reproducing HCV infection and ethanol treatment in HCC cells. Interestingly, HCV and alcohol increased the expression of Cyclin B, Aurora kinase A, and tyrosine-phosphorylated gamma-tubulin also in tissues from patients with HCV- or alcohol-related HCCs. In vitro models suggest that HCV requires the expression of PKR (RNA-activated protein kinase), as well as JNK (c-Jun N-terminal kinase) and p38MAPK (p38 mitogen-activated protein kinase) proteins; while, ethanol bypasses all these pathways. Our results support the idea that HCV and alcohol may promote oncogenesis by acting through the same mitotic proteins, but via different signaling pathways.